2005
DOI: 10.1007/s10433-005-0006-9
|View full text |Cite
|
Sign up to set email alerts
|

Disability-free life expectancy of older French people: gender and education differentials from the PAQUID cohort

Abstract: In countries with low mortality rates, the quality of the years of life is more important to consider than total life expectancy (TLE). Disability-free life expectancy (DFLE) is one of the most relevant indicators of health and the quality of life. This paper aims to estimate TLE and DFLE with four levels of severity of disability and to explore gender and educational differences in older French people. In this cohort study, four levels of disability severity were distinguished, disability being evaluated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
(49 reference statements)
2
13
0
Order By: Relevance
“…More recent studies confirm this finding (Majer et al 2010;Bronnum-Hansen et al 2004;Bronnum-Hansen and Baadsgaard 2008;Matthews, Jagger, and Hancock 2006;Matthews et al 2009;Minicuci and Noale 2005;Pérès et al 2005;Van Oyen et al 2005;Lievre, Alley, and Crimmins 2008;Bossuyt et al 2004). Although these studies have already illustrated the unequal share of life between years in good and poor health, they are often of limited utility in the debate concerning the prolongation of working life.…”
Section: Health Expectancy Differentials: Context and New Insightsupporting
confidence: 54%
See 1 more Smart Citation
“…More recent studies confirm this finding (Majer et al 2010;Bronnum-Hansen et al 2004;Bronnum-Hansen and Baadsgaard 2008;Matthews, Jagger, and Hancock 2006;Matthews et al 2009;Minicuci and Noale 2005;Pérès et al 2005;Van Oyen et al 2005;Lievre, Alley, and Crimmins 2008;Bossuyt et al 2004). Although these studies have already illustrated the unequal share of life between years in good and poor health, they are often of limited utility in the debate concerning the prolongation of working life.…”
Section: Health Expectancy Differentials: Context and New Insightsupporting
confidence: 54%
“…LE 50 with ADL restrictions reflects periods over which care and assistance are required: it is around three years for manual workers and two years for the highly qualified occupations. A study of a French elderly cohort (PAQUID) measured educational differentials in HE and concluded that there is probably an incompressible minimum period of time at the end of life to be lived with severe disability such as ADL restrictions, whatever the social status (Pérès et al 2005). Small absolute differentials in LE 50 with ADL restrictions mean large differentials in LE 50 without ADL restrictions: almost six years for men and three and a half years for women.…”
Section: Various Health Situations and Varying Differentialsmentioning
confidence: 99%
“…However, few go beyond the mere description and explore the role of determinants on the gender difference (Bélanger et al 2005;Crimmins et al 2002;Pérès et al 2005). The aim of this article is to describe the pattern of the gender difference in life expectancy, the life expectancy with and without activity limitations at age 50 across 25 EU countries and to explore the association with macro-level factors that may explain any diversity in gender difference in life expectancy with activity limitations between countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear whether the years gained are years in good health or years lived with disability and in need of help [ 1 ]. In this light, the quality of the extra years of life is more important than overall life expectancy [ 2 ]. Indeed, 'adding life to the years' has become a key concept of 'successful ageing' [ 3 ], itself a prominent theme in contemporary applied gerontology [ 4 ].…”
Section: Introductionmentioning
confidence: 99%